The Yugoslav Minority Standards and Croats in the FR of Yugoslavia - Milenko Horvatić (Migracijske i Etniĉke Teme, 2001)
Ethnic relations and the treatment of minorities have proven themselves to be an exceptionally important issue for security and stability in the Balkans, especially in the Federal Republic of Yugoslavia (FRY). The perspective for peace in this country is to a great deal dependent on the ability to find a solution to the problems of national minorities. All Yugoslav constitutions have included clauses relating to minority rights, yet significant differences were evident in the degrees of stipulated protection for minorities. In these acts minority status was regulated as a liberty and a right enjoyed by individuals − members of minorities. The status of a minority as a collective group was generally not regulated, and the measures for the protection of collective rights were not sufficiently developed. Nevertheless, guarantees in the Constitution of the FRY and the fact that international accords in the Yugoslav legal system stand above the law, on the whole provide a good basis for developing a system of protection of minority rights. Croats live on the territory of the present FRY as an indigenous and homogeneous group in the republics of Serbia and Montenegro. In Serbia the largest Croat concentration is located in the Autonomous Province of Vojvodina. Following the Kosovo crisis, no Croats remained in Kosovo. In Montenegro Croats live mostly in Boka Kotorska. Minorities make up a third of the population of the FRY and the largest minority groups live in Serbia. Based on an analysis of census figures after WWII (the period examined) it is apparent that the number and percentage of minority group members has been on a continuous decline, except in the case of the Albanians, Roma and Yugoslavs. The national (ethnic) structure of the FRY has significantly changed since the 1991 census, to the detriment of the percentage of minority populations in the overall population. Taking into consideration the period from 1961 to the (most recent) 1991 census, the number of Croats in the F.R. has fallen by 45%. A reduction of such scale fall in the number of members of a non-titular group in a Yugoslav republic was not witnessed in any other republic of the former Socialist Federal Republic of Yugoslavia. Such a significant reduction in the number of members of a people, along with an overall population increase during the examined period, has been the result of state policy measures, as well as of objective circumstances. After the break-up of the former Socialist Federal Republic of Yugoslavia, Croats in the FRY found themselves in the position of a national minority, although this status has not been recognised in their case to this day. According to all criteria applied in determining minority status, Croats in the FRY should have gained this right and status, since the existence of minorities, with all their characteristic minority traits, is an objective fact that no state with European ambitions can endlessly ignore.